Tourism and regional development: a study in the State of São Paulo - Aulicino, Madalena Pedroso (Revista Turismo em Análise, 2011)
The purpose of this article is to demonstrate that tourism may be a regional development factor. From a theoretical perspective, regional problems were surveyed and, to make the study operational, the concepts relating to goods and products that are characteristic of tourism were recovered, according to the parameters of the World Tourism Organization (WTO). The assumption that touristic activity may be a regional development factor was established and, to confirm it, the author selected two sets of State of São Paulo municipalities, differentiated by the presence or not of touristic activity. Municipal data were then assessed based on the Regional Economic Base Theory's Location Quotient formula that measures the concentration of an activity in a certain area in relation to the distribution of such activity throughout a geographic space that comprises it. In the case of the municipalities, the Location Quotient was applied to the data of jobs created in hotels, therefore demonstrating that tourism may be a regional development factor, based on the established parameters.